Nilai Pendidikan Karakter pada Tindak Tutur Ilukosi dalam Podcast Deddy Corbuzeir Bersama Syekh Ali Jaber - Rudi; Joko Widodo (GERAM: Gerakan Aktif Menulis, 2021)
This study aims to describe the types of illocutionary speech and the value of character education in the speech on the video podcast of Deddy Corbuzier with Syekh Ali Jaber. This type of qualitative research with a descriptive approach. Sources of research data are utterances spoken by Deddy Corbuzier, Syekh Ali Jaber, and Gus Mifta in Deddy Corbuzier's Podcast video with Syekh Ali Jaber on Deddy Corbuzier youtube channel. The research data is in the form of sentences that reflect illocutionary speech acts and the value of character education. The data collection technique is done by using observation technique. The data analysis technique uses the Miles and Huberman model, which includes the stages of data reduction, data presentation, and conclusion/verification. The results showed: (1) types of illocutionary speech acts include assertive, directive, commissive, and expressive speech acts. (2) The value of character education includes the character of social care, religion, honesty, tolerance, love for the country, creativity, democracy, and love peace. Based on the findings, the dominant character education value in the speech activity is the value of religious character. This can happen, because it is influenced by the background of the speaker and the context of the speech.